Phase 1 and pharmacodynamic trial of everolimus in combination with cetuximab in patients with advanced cancer. Issue 1 (24th September 2013) - Ciunci, Christine A.; Perini, Rodolfo F.; Avadhani, Anjali N.; Kang, Hyunseon C.; Sun, Weijing; Redlinger, Maryann; Harlacker, Kathleen; Flaherty, Keith T.; Giantonio, Bruce J.; Rosen, Mark A.; Divgi, Chaitanya R.; Song, Hee Kwon; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Preclinical and clinical studies suggest mTOR (mammalian target of rapamycin) inhibitors may have metabolic and antiangiogenic effects, and synergize with epidermal growth factor pathway inhibitors. Therefore, a phase 1/pharmacodynamic trial of everolimus with cetuximab was performed. METHODS A total of 29 patients were randomized to a run‐in of oral everolimus (30, 50, or 70 mg) or cetuximab (400 mg/m2 loading, 250 mg/m2 maintenance) weekly, followed by the combination in this dose‐escalation study. Primary endpoints were phase 2 dose and toxicity characterization. [18F]Fluorodeoxyglucose positron emission tomography (FDG‐PET) was performed as a pharmacodynamic marker of mTOR inhibition, and dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) was performed as an indicator of tumor perfusion changes, at 3 time points. RESULTS Everolimus and cetuximab were tolerable at full doses, with an expected toxicity profile. Dose‐limiting toxicities in the everolimus 70 mg group included grade 3 skin toxicity in 2 patients, and mucositis in 1 patient. Of 16 patients evaluable for response, 5 had stable disease lasting 4 to 19 months. Mean change in maximum standardized uptake value (SUVmax) for those treated initially with everolimus was −24% (2% to −54%), and with cetuximab was −5% (−23 to 36%). The Ktrans measured by DCE‐MRI did not decrease, regardless of run‐in drug. CONCLUSIONS Everolimus and cetuximab can be safely administered at standard doses, and are associated with prolonged disease control. The recommended phase 2 dose of oral weekly everolimus is 70 mg in combination with standard cetuximab. Imaging studies reveal that metabolic inhibition by everolimus alone and in combination with cetuximab predominates over changes in tumor perfusion in this patient population. Cancer 2014;120:77–85. © 2013 American Cancer Society.